Reliability index of critical thinking among electrical technology teachers - Hizwan Mohd Hisham, Mohd; Kamin, Yusri; Sukri Saud, Muhammad (International Journal of Engineering and Technology, 2018)
This paper aims to determine the reliability index for critical thinking among electrical technology teachers in vocational colleges. Teachers are the backbone of the education system in technical education and the executor of the policies and goals that have been set by the government through the Ministry of Education. Critical thinking is one of the higher order thinking skills that involves both cognitive skills and dispositions. Empirical research suggest that people begin developing critical thinking at a very young age. Teachers are thus urged to provide explicit instruction in critical thinking to teach how to transfer knowledge critically to students. In order to transfer critical thinking, the teacher should be infused with the sub-skills that contribute to the development of critical thinking.Â Â